2022
DOI: 10.1088/1757-899x/1238/1/012071
|View full text |Cite
|
Sign up to set email alerts
|

Control of draw-in in the deep-drawing process by regulating the force on the blank holder

Abstract: Sheet metal forming processes are strongly influenced by process parameters, moreover fluctuations during the process and in material properties often lead to robustness problems. Therefore, numerical simulations as a function of design and noise parameters are usually adopted to detect ahead critical regions. To ensure efficiency and quality, the new era of industry 4.0 aims to develop systems that can control critical issues online. The aim of this work is developing a methodology that allows to adjust the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Conversely, excessive BHG can lead to the formation of wrinkles in the product. The research conducted by Palmieri et al [18] confirmed the findings of this study, demonstrating that the force applied to the blank holder, represented by the BHG value in this case, significantly affects the achievement of an optimal draw-in profile and the production of a defect-free product. Generally, the blank holder gap should be set to provide sufficient restraint on the blank without causing excessive friction or wrinkling.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Conversely, excessive BHG can lead to the formation of wrinkles in the product. The research conducted by Palmieri et al [18] confirmed the findings of this study, demonstrating that the force applied to the blank holder, represented by the BHG value in this case, significantly affects the achievement of an optimal draw-in profile and the production of a defect-free product. Generally, the blank holder gap should be set to provide sufficient restraint on the blank without causing excessive friction or wrinkling.…”
Section: Resultssupporting
confidence: 88%
“…The deep drawing value is within the safe limit range, which is according to Equations ( 9) and (10), and the critical deep drawing force limit is according to Equations ( 11) and ( 12) so that the product can avoid cracks and wrinkles. The experimental results indicate that implementing both the BHF [18] and the BHG yields similar outcomes. However, the BHG system is significantly easier to use while effectively controlling material flow and preventing issues such as cracking and wrinkling defects.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The action of the blank holder can prevent defects on the drawn component such as cracks, wrinkles and thinning [1][2]. Therefore, one of the design parameters affecting the drawing process is the force on the blank holder [3][4]. In fact, it has been shown that an increase in the force on the blank holder can lead to a reduction in wrinkles.…”
Section: Introductionmentioning
confidence: 99%
“…To attain a reproducible and automated adjustment of the process, many authors proposed implementing a feedback-type control systems [21][22][23][24][25][26][27][28][29]. In this type of control, it is crucial to identify a parameter for in-line monitoring, such as the sliding of the blank.…”
Section: Introductionmentioning
confidence: 99%